IMPLEMENTATION OF SHARIA ECONOMIC PRINCIPLES IN THE GLOBALIZATION ERA - Rahmani, Zikri; Rozi, Rozi; Fitriyanti, Eka; Iqbal, M; Karimullah, Suud Sarim (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2023)
The globalitation era is an era that requires people to quickly adapt to the times that are increasingly advancing rapidly. Because if it is not adaptive it will be a human being left behind. While the era of globalization demands a tight contestation. Especially in the economic sector. Every global company has its own strategy in marketing its business. They don't think about the fate of their competitors. That's because they think that other companies are tough competitors. So that their competition prioritizes individual (company) profits and stops other companies that have the same business product. Of course, this global business competition is contrary to the principles of Islamic economics. Which, the principles of Islamic economics are not solely seeking individual gain. But also think about mutual benefits. Therefore, there are at least three Islamic economic principles that must exist even in the midst of global business competition, namely multiple ownership, freedom to act, and social justice. These three basic principles of Islamic economics must still exist in economic behavior and remain relevant even in the midst of global economic contestation.